ANALISIS KEPUASAN MIE STEVEN DI PASAR PINASUNGKULAN KAROMBASAN MANADO - Natalia J. Umboh; Charles R. Ngangi; Celsius Talumingan; Lorraine Sondak (Universitas Sam Ratulangi, 2015)
ABSTRACT This study conducted to determine noodles customer satisfaction the generally seen from the aspect of the product, price, place and service. Research carried out for two months the January 2015 to March 2015 from preparation to making the report. Research was conducted in Pinasungkulan market Manado Karombasan in this case Mie Steven factory, which is focus of consumers who directly buy noodles. Data collected by using the primary data and secondary data. Primary data was obtained directly through direct interviews with consumers who buy noodles by using a list of questions / questionnaire that has been prepared, while the secondary data obtained from related companies of this study, the data analyted using quantitative analysis. Data were measured using a customer satisfaction index (Customer Satisfaction Index). The results showed that the Consumers Statisfaction Index Average of Product, Price, Place and service is satisfied with customer satisfaction index of 72.95 percent. It means that the product, price, service has to meet consumer expectations, while the place has not keep the expectations of consumrs because respondents mean provide an assessment quite satisfied.